An ALMA Observation of Time Variations in Chromospheric Temperature of a Solar Plage Region - Abe, Masashi; Shimizu, Toshifumi; Shimojo, Masumi (Frontiers in Astronomy and Space Sciences, 2022)
Nanoflares and the shock formation of magnetohydrodynamic waves in the solar chromosphere have been considered as key physical mechanisms of the heating of the chromosphere and corona. To investigate candidates of their signature in the mm-wavelength, a tiny active region located on the solar disk was observed with the Atacama Large millimeter and sub-millimeter Array (ALMA) at 3 mm, coordinated with observatories on orbit including Hinode SOT spectro-polarimeter in the Cycle 4 solar campaign (March 19, 2017). ALMA’s spatial resolution was moderate, far from the best performance, but it provided stable conditions that are suitable to investigate temporal variations in the mm-wavelength. We determined that the noise level is less than 20 K (σ) over one hour in the 20-s cadence time series of synthesized ALMA images. The time variations with amplitudes above the noise level were observed throughout the field of view, but variations exceeding 200 K, corresponding to energy input to the chromosphere on the order of 1020−22 erg, were localized in two locations. One location was on the polarity inversion line, where tiny concentrated magnetic patches exist in weak field and a tiny magnetic flux may be emergent. The other location was at the outer edge of a bipolar magnetic region, which was under development with a successive series of magnetic flux emergence. This observation suggests that nanoflare-class energy inputs in the chromosphere can occur associated with emerging flux activities.